Optimisation of the glycerol-to-ornithine molar ratio in the feed medium for the continuous production of clavulanic acid by Streptomyces clavuligerus - Domingues, Leticia C. G. [UNESP]; Teodoro, Juliana C.; Hokka, Carlos O.; Badino, Alberto C.; Araujo, Maria Lucia Gonsales da Costa [UNESP] (Elsevier B.V. Sa, 2010)
Amino acids are well metabolized by Streptomyces clavuligerus during the production of clavulanic acid using glycerol as main carbon and energy source. However, only a few amino acids such as arginine and ornithine are favorable for CA biosynthesis. The aim of this work was to optimize the glycerol:ornithine molar ratio in the feed medium containing only these compounds to maximize CA production in continuous cultivation. A minimum number of experiments were performed by means of a simple two-level full-factorial central composite design to investigate the combined effect of glycerol and ornithine feeding on the CA concentration during the intermittent and continuous process in shake-flasks. Statistical analysis of the experimental data using the response surface methodology showed that a glycerol-to-ornithine molar ratio of approximately 40:1 in the feed medium resulted in the highest CA concentration when fermentation was stopped. Under these optimized conditions, in bench-scale fermentor runs, the CA concentration reached more than double the concentration obtained in shake-flasks runs. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Clavulanic acid; Submerged culture; Streptomyces clavuligerus; Continuous culture; Glycerol; Ornithine; Bioprocess design; Optimisation